Analisis Komparasi Teori Belajar: Paduan Teori Belajar Dalam Perspektif Barat (Konvensional) Dan Islam - Hosen; Mukit, Abdul (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
So far, learning theory has mostly come from the West, which has a different orientation from Islam. It is unfortunate that Muslims adopt these theories uncritically. Even in universities labeled as Islamic, they still use western (conventional) learning theory as the only main reference in their learning. This research is descriptive qualitative with comparative analysis. The data for this study uses primary data sources, namely the West and the Koran and al-Hadith (Islam). The data collection technique uses the documentation method. The data analysis technique uses content analysis. While the discussion uses the method of deduction, induction, and comparison The conclusion that can be drawn is that there are fundamental differences between Western and Islamic learning theories because of different views on world problems. The West places more emphasis on learning events that are rational-empirical-quantitative based on the secular-positivistic-materialistic Western worldview. Meanwhile, Islamic learning theory does not only provide accentuation on rational-empirical learning events, but the theory also emphasizes normative-qualitative learning events originating from the Qur'an and al-Sunnah as well as Islamic intellectual treasures developed by Muslim scholars in Indonesia.